India : Unlocking Opportunities for Forest-Dependent People in India, Volume 1, Main Report - World Bank (Washington, DC, 2012)
This study by the World Bank indicates that forests offer vast potential for poverty reduction and rural economic growth in India while also supporting critical national conservation goals. An estimated 275 million people in rural areas depend on forests for at least part of their livelihoods. Forest dwellers, which include a high proportion of tribals, are among the poorest and most vulnerable groups in society. The government of India has adopted Joint Forest Management as a principal approach for community-based forestry. The program now covers 27 percent of the national forest area across 27 states, and encompasses 85,000 village committees. Over the past decade, the Joint Forest Management model has been evolving from an approach heavily oriented towards commercial timber managed by state forest departments (with communities providing labor), to an approach more supportive of forest conservation with communities sharing benefits in return for assisting with limited management activities. Although this transition has been successful by some measures, most communities still fail to utilize the full potential of forests to improve local livelihoods. Forests are mainly used as a safety net during difficult economic periods, or for seasonal subsistence products like fuelwood and fodder. For communities to better exploit the untapped potential of forests, wide ranging and carefully phased reforms are required at both the national and state levels addressing: 1) stronger forest rights and responsibilities for forest communities; 2) more effective management systems targeted at communities involved with forestry; 3) improved access to more efficient market systems for major and minor products; and 4) more effective and flexible institutions and capacities.